Membumikan Lesson Study dalam Meningkatkan Kemampuan Mengajar Guru melalui Strategi Difusi Inovasi di SMP Negeri 3 Madiun - Umi Nur Hasanah; Vera Desy; Mambaul Ngadimah; Syafiq Humaisi (Excelencia: Journal of Islamic Education & Management, 2023)
Lesson Study is a model of fostering the educational profession through collaborative and continuous learning studies based on the principles of legality and mutual learning to build learning communities. This research will describe how the innovation divusi process can cultivate Lesson study activities at SMP Negeri 3 Madiun The results of this study show that the emergence of understanding and persuasion from lesson study activities is built through morning and afternoon breefing carried out by the principal. Decision making for lesson study activities begins through deliberations with staff and teachers in official meeting forums. The implementation of lesson study activities is carried out on a scheduled basis with the target that each teacher will become a model teacher once a year .Thus each semester targets 17 teachers who will become model teachers. Confirmation of lesson study is carried out when the lesson study activity is completed by producing a decision that lesson study activities have a huge impact in increasing understanding of the material, learning methods, improving the ability to observe learning and with lesson study can be improved the colegality system in finding quality learning